POTENSI PEMANFAATAN SLAG ALUMINIUM SEBAGAI SUBSTITUSI SEMEN DALAM PROSES STABILISASI/SOLIDIFIKASI LIMBAH B3 DENGAN KAJIAN PUSTAKA (STUDI KASUS : PT.X KECAMATAN KESAMBEN, JOMBANG) - Komang Ardya Putri Saraswati; Mohammad Razif (Envirotek : Jurnal Ilmiah Teknik Lingkungan, 2020)
According to PP 101 Year 2014, aluminum slag is classified as BTS waste in code B313-2 and thus, will bring chronicle effects. This research aimed at investigating the potentials of aluminum slag by analyzing the waste characteristics, solidification process, compressive strength, and TCLP of BTS waste solidification product. The results of research demonstrated that the slag contained BTS elements and based on PP 101 Year 2014, they must be managed, one of which is through stabilization/solidification. The process of using aluminium slag waste solidification in this research was conducted by crushing, grinding, sorting from aluminium dross and recovering metal via smelting. Slag has potentials for construction materials such as geopolymer concrete, concrete brick, pressed brick, and paving block. The best composition for using aluminium slag with solidification is less than 20% because the product will get leaching. The highest compressive strength of slag by 36.8 Mpa at X Ltd in Jombang was for paving block of parking area. In addition, TCLP test toward aluminium slag has fulfilled USEPA standard and it is safe for the environment in the long period. Keywords: aluminium slag aluminium, solidification, compressive strength, TCLP